2015
DOI: 10.1080/13854046.2015.1077995
|View full text |Cite
|
Sign up to set email alerts
|

Does Older Age Confer an Increased Risk of Incident Neurocognitive Disorders Among Persons Living with HIV Disease?

Abstract: Objective This study aimed to determine the combined effects of age and HIV infection on the risk of incident neurocognitive disorders. Method A total of 146 neurocognitively normal participants were enrolled at baseline into one of four groups based on age (≤ 40 years and ≥ 50 years) and HIV serostatus resulting in 24 younger HIV−, 27 younger HIV+, 39 older HIV−, and 56 older HIV+ individuals. All participants were administered a standardized clinical neuropsychological battery at baseline and 14.3 ±0.2 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 60 publications
(75 reference statements)
3
46
0
Order By: Relevance
“…65,66 Age X HIV interactions were not the primary focus of these WIHS neurocognitive studies, but in general, the larger HIV literature does not show strong interaction effects, although there are strong trends in showing more neurocognitive impairment in older adults with HIV. 67,68 …”
Section: Discussionmentioning
confidence: 99%
“…65,66 Age X HIV interactions were not the primary focus of these WIHS neurocognitive studies, but in general, the larger HIV literature does not show strong interaction effects, although there are strong trends in showing more neurocognitive impairment in older adults with HIV. 67,68 …”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies are necessary to better understand the inter-individual patterns of PM changes and associated consequences for various aspects of everyday functioning (e.g., Tucker-Drob, 2011). As recent findings suggest that PM decline may be an early indicator of incident neurocognitive disorders (e.g., Sheppard et al, in press), these data warrant further investigation of potentially moderating effects of compensatory strategies to maintain independence and enhance daily functioning in older adults.…”
Section: Discussionmentioning
confidence: 87%
“…Prior studies have investigated the incidence of neurocognitive impairment using the Frascati criteria (e.g., Sheppard et al, 2015), however, there have been no studies that examine the DSM-5 guidelines from a longitudinal perspective and additionally, no studies have directly compared the rates of observed changes (or lack thereof) across these diagnostic guidelines. Results show similar rates of both stable classification and incident neurocognitive disorder between the Frascati and Gisslén criteria.…”
Section: Discussionmentioning
confidence: 99%